2009
DOI: 10.1002/cncr.24359
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine sulfate liposomes injection (Marqibo) in heavily pretreated patients with refractory aggressive non‐Hodgkin lymphoma

Abstract: BACKGROUND: Marqibo, a sphingosomal/cholesterol encapsulation of vincristine sulfate has targeted, increased, and sustained delivery of vincristine to tumor tissues. A phase 2, open‐label, single‐arm, and multinational study evaluated the efficacy and tolerability of Marqibo as a single agent in patients with multiply relapsed or refractory aggressive non‐Hodgkin lymphoma (NHL). METHODS: Eligible patients had relapsed or refractory de novo or transformed aggressive NHL and prior treatment with at least 2 multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(55 citation statements)
references
References 10 publications
0
53
0
Order By: Relevance
“…Previous studies have demonstrated that the liposomal encapsulation of VCR increased its antitumor efficacy without increasing toxicity [8][9][10][11] . Marqibo ® (Vincristine sulfate liposomes injection, Hana Biosciences, Inc) has been extensively studied for its capability to prolong the pharmacokinetics and subsequent exposure of VCR to cancer cells [5,6,12] , thus increasing its antitumor activity [5,13,14] . However, Marqibo ® was developed as a 3-vial kit containing 100 mg/mL of injectable sphingomyelin/cholesterol liposomes, 14.2 mg/mL of injectable sodium phosphate and Oncovin (injectable vincristine sulfate).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the liposomal encapsulation of VCR increased its antitumor efficacy without increasing toxicity [8][9][10][11] . Marqibo ® (Vincristine sulfate liposomes injection, Hana Biosciences, Inc) has been extensively studied for its capability to prolong the pharmacokinetics and subsequent exposure of VCR to cancer cells [5,6,12] , thus increasing its antitumor activity [5,13,14] . However, Marqibo ® was developed as a 3-vial kit containing 100 mg/mL of injectable sphingomyelin/cholesterol liposomes, 14.2 mg/mL of injectable sodium phosphate and Oncovin (injectable vincristine sulfate).…”
Section: Introductionmentioning
confidence: 99%
“…The liposomal formulation of vincristine made by Talon was registered under trade name of Marqibo. Marqibo was approved in 2012 by the FDA for the treatment of acute lymphoblastic leukemia (Sarris et al 2000;Rodriguez et al 2009). Celator Pharmaceuticals Inc developed CPX-351, a liposomal formulation of cytarabine and daunorubicin.…”
Section: Applications Of Liposomes In Cancermentioning
confidence: 99%
“…The ORR was 14%. In the pivotal phase II study of SM/Chol liposomal vincristine, 119 patients with multiple relapsed or refractory aggressive NHL were treated intravenously at 2 mg/m 2 every two weeks to estimate the therapeutic effect and tolerability of this formulation (Rodriguez et al, 2009). The ORR was 25% and showed approximately twice the dose intensity tolerability compared to vincristine solution.…”
Section: Combination Therapymentioning
confidence: 99%